The processed Sanguisorba officinalis L. triterpenoids prevent colon cancer through the TNF-α/NF-κB signaling pathway, combined with network pharmacology, molecular simulation dynamics and experimental verification - Gan, Chunli; Mu, Yuanqiu; Ali, Shah Syed Faizan; Shi, Xuepeng; Jiang, Shuang; Wang, Zhengyang; Wu, Xiaotian; Wang, Xiaotong; Wang, Zhibin; Zhang, Shulu; Feng, Zheng; Yang, Chunjuan (Frontiers in Immunology, 2025)
BackgroundSanguisorba officinalis L. (S.L.), a traditional Chinese medicine from the Rosaceae family, is recognized for its rich content of triterpenoids, which are known for their antioxidant, anti-inflammatory, and anti-tumor properties. Although its traditional uses and biological activities are well known, its role in preventing colon cancer and the underlying mechanisms remain unclear. This study aims to elucidate the preventive mechanisms of triterpenoids in both raw (TR) and processed (TP) forms of S.L. against colon cancer.MethodsThe AOM/DSS-induced mouse model of colon cancer was employed to elucidate the mechanism underlying the preventive effects of Sanguisorba officinalis L. triterpenoids (ST) against colon cancer. A comprehensive suite of techniques, including hematoxylin-eosin staining (H&E), immunohistochemistry (IHC), TUNEL staining, Western blotting (WB), and DNA methylation analysis, was utilized to investigate the preventive effects of ST on colon cancer. The main active compounds were identified using UPLC-Q-TOF-MS, and potential active compounds were screened through network pharmacology and molecular docking. The stability of the protein-ligand complexes was further assessed using molecular dynamics simulations.ResultsIn vivo experiments, treatment with ST significantly improved the clinical manifestations, Disease Activity Index (DAI) scores, and pathological lesions associated with colon cancer, with all drug administration groups outperforming the model group. Additionally, ST markedly enhanced gut barrier function by downregulating the levels of TNF-α, p65, COX-2, and iNOS. Furthermore, ST dramatically ameliorated the colonic immune-inflammatory state, which was associated with decreased expression of proliferative proteins and increased expression of apoptotic proteins. Among the identified triterpenoids, compound 27 May be the main active compound. Notably, compound 27 can form a stable complex with TNF-α.ConclusionThese results suggest that TP has a more pronounced colon cancer prevention effect than TR. TP play a role in preventing colon cancer by down-regulating TNF-α and thereby inhibiting the NF-κB signaling pathway. This research not only fills the mechanism gap of S.L. in the field of colon cancer prevention, but also provides methodological support and theoretical foundation for its transition from traditional Chinese medicine to clinical practice through the integration of multi-disciplinary technologies and the verification of precise targets.